2017
DOI: 10.1016/j.jallcom.2016.10.095
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of Co-N thin films deposited using magnetron sputtering at 523 K

Abstract: In this work, we studied cobalt nitride (Co-N) thin films deposited using a dc magnetron sputtering method at a substrate temperature (T s ) of 523 K. We find that independent of the reactive gas flow (R N 2 ) used during sputtering, the phases of Co-N formed at this temperature seems to be identical having N at.% ∼5. This is contrary to Co-N phases formed at lower T s . For T s ∼300 K, an evolution of Co-N phases starting from Co(N)→Co 4 N→Co 3 N→CoN can be seen as R N 2 increases to 100%, whereas when the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…2) indicating that N out-diffuses almost completely from CoN. The implication of high T s on Co-N phases was also amply demonstrated recently [33]. Here, it was shown that when Co was sputtered with different amounts of N 2 (and even with N 2 alone) at 523 K, the resulting phase obtained was always fcc Co, independent of the amount of N 2 that was used during the deposition [33].…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…2) indicating that N out-diffuses almost completely from CoN. The implication of high T s on Co-N phases was also amply demonstrated recently [33]. Here, it was shown that when Co was sputtered with different amounts of N 2 (and even with N 2 alone) at 523 K, the resulting phase obtained was always fcc Co, independent of the amount of N 2 that was used during the deposition [33].…”
Section: Resultssupporting
confidence: 61%
“…We find that in previous works the Co 4 N phase was always synthesized at T s 525 K [20][21][22][23][24][25][26][27]. Comparing the LP of Co 4 N films obtained in those works, we find that the LP was much smaller than the theoretically predicted value of 3.735 Å [18] [20,33]. In several other studies also, when T s > 525 K, LP remained at 3.54 Å [21,22].…”
Section: Resultsmentioning
confidence: 44%
See 2 more Smart Citations
“…Theoretical values of enthalpy of formation (∆H • f ) for Fe 4 N is about -12 kJ mol −1 [22], whereas those for Co 4 N are slightly above or below 0 for hcp Co or fcc Co [11]. This also implies that at a higher T s , Co 4 N system will be less stable as compared to Fe 4 N. In a recent work, we studied the phase formation process in the Co-N system at T s = 300 K [23] and 523 K [24]. We found that at T s = 523 K, N incorporation in the Co-N system is minimal and the phases formed are similar to a fcc Co having LP∼3.52Å.…”
Section: Introductionmentioning
confidence: 99%